Breastfeeding Practices among Mothers in a Selected Semi-Urban Area of Bangladesh - Doha, Maheen; Begum, Meherunnessa; Akhter, Nasreen; Khan, Sabara Syeda; Chowdhury, Syeda Shara; Sharmin, Tanima (Delta Medical College Journal, 2020)
Background: Breastfeeding is one of the most important factors for growth and development of infants. It protects both mothers and children against various infections and diseases. Objective: To identify the demographic variables related to breast feeding practices among mothers of below five years children in a semi-urban area of Bangladesh. Materials and methods: It was a descriptive type of cross sectional study conducted among purposively selected 180 mothers of below five years children. The study was conducted at Safipur, Kaliyakor, Gazipur in Bangladesh from 12th to16th February, 2019. Data were collected with a semi structured questionnaire by face to face interview. Statistical package for social science 19.0 programme was used for data analysis. Results: Most of the respondents (91.67%) knew about colostrum and among them (94.55%) fed their child colostrum immediately after birth. Majority of the respondents (95.56%) had knowledge about exclusive breastfeeding and most of them (65.70%) knew that the duration of exclusive breastfeeding is up to 6 months. Almost all of the respondents (94.44%) knew about weaning practices and most of them (70.59%) started weaning at the age of 6 months. Almost all respondents (89.44%) could breastfeed their child properly. Majority of the respondents (76.67%) knew that breast milk provides immunity to their children against certain diseases. Most of the respondents (73.33%) gathered knowledge about breastfeeding practices from their family members. Conclusion: Appropriate awareness about exclusive breast feeding among the mothers will help in enhancing the growth and development of children and also in saving them from many disease. Delta Med Col J. Jul 2020;8(2): 61-66